Anthraquinone-Catalyzed Photooxidation of Boronic Acids in a Bio-Based Solvent (2-Me-THF) - Gkizis, Petros L.; Serviou, Stamatis K.; Balaskas, Angelos; Constantinou, Constantinos T.; Triandafillidi, Ierasia; Kokotos, Christoforos G. (Synlett, 2023)
The phenol moiety appears in a wide variety of natural products, exhibiting biological activity, and in numerous active pharmaceutical compounds. Boronic acids are potential precursors of the phenol scaffold, and a plethora of efforts has been focused in developing novel and green protocols, targeting their chemoselective transformation into phenols. Photochemistry is a rapidly expanding research field converting light energy into chemical potential. Photochemical aerobic processes possess additional advantages to photochemistry and may find applications in chemical industries. Herein, a low-catalyst-loading anthraquinone-catalyzed photochemical process is demonstrated, under CFL lamp irradiation, while exploiting 2-Me-THF as the reaction medium for the conversion of boronic acids into phenols. Furthermore, a broad substrate scope was employed.
Keywords: photochemistry; aerobic oxidation; green chemistry; boronic acid; anthraquinone